An investigation of the mechanical behaviour of fine tubes fabricated from a Ti–25Nb–3Mo–3Zr–2Sn alloy. (15th November 2015) - Zhang, Yaowu; Kent, Damon; Wang, Gui; St John, David; Dargusch, Matthew
Abstract: This study investigates the mechanical properties and the deformation mechanisms active in Ti–25Nb–3Mo–3Zr–2Sn fine tubes. Ti–25Nb–3Mo–3Zr–2Sn alloy is a recently developed metastable β titanium alloy intended for biomedical applications. Tensile tests were carried out on the fine tubes. The modulus of the Ti–25Nb–3Mo–3Zr–2Sn fine tubes increased with reductions in the diameter for tubes in the cold rolled and annealed conditions. In comparison with cold rolled tubes, the annealed tubes exhibit increased strain hardening behaviour and superior ductility. Mechanical twins, stress-induced martensitic transformation and the textures of the β and α″ phases were investigated. The results show that the fine tubes exhibit different moduli which are related to the evolution of β and α″ phase textures during processing. Cold rolling facilitates the transformation from β to the α″ phase and mechanical {332}〈113〉 twinning. For the annealed tubes, mechanical twinning as well as primary and secondary martensitic transformations was activated at specific levels of tensile strain. Twins developed with increasing levels of strain, and secondary martensitic transformations occurred within the twinned β regions. Annealed fine tubes exhibit multistage strain hardening behaviour and superior ductility due to the synergetic effects of twinning induced plasticity and transformation induced plasticity during tensile deformation. Graphical abstract: Highlights: The modulus was increased with reductions in the diameter of β-Ti fine tubes. The development of β and α″ phase texture resulted in an increased modulus. The simultaneously active TRIP and TWIP contribute to the excellent tensile ductility and the high level of strain-hardening.